KEPATUHAN SYARIAH (SHARIA COMPLIANCE) AKAD MUDHARABAH DI BMT BIM - Ainin Ainiyah; A. Syifa'ul Qulub (Universitas Airlangga, 2019)
The purpose of this study is to know the compliance of shariah mudharabah agreement in financing products offered by BMT BIM Rengel branch. Things that need to be reviewed in mudharabah contract practice are adjusted to the points contained in the National Shariah Council Fatwa of Indonesian Council of Ulama (Fatwa DSN-MUI) No.07 / DSN-MUI / IV / 2000 on mudharabah financing. This research uses qualitative method with descriptive case study strategy. The object of this research is BMT BIM Rengel branch, Tuban. By conducting interviews to three respondents consisting of marketers, branch leaders, and mudharabah customers BMT BIM branch Rengel. After interviews, the results of the study were analyzed using pattern matching to get the conclusion. The results of the research conducted by observations and interviews by the researchers to the three respondents that mudharabah contract operation on financing products in BMT BIM Rengel branch has met the compliance of sharia, this is adjusted with the Fatwa DSN-MUI No.07 / DSN-MUI / IV / 2000 about mudharabah financing in which there are three points of equity, namely the provision of financing, harmonious and mudaraba conditions, and mudharabah financing law. Implementing this compliance benefits the various parties involved.Keywords: Sharia Compliance, BMT BIM, Mudharabah, Fatwa DSN-MUIREFERENCES Abidin, I.1987. Radd al-Mukhtar 'ala al-Durr al-Mukhtar. Beirut: Dar Ihya al-Turas.Al-Bahuti. kasyasyaf Al-Qina. Beirut: Dar Al-Fikr.Al-Nawawi. Riyadh al-Shalihin. Beirut: Dar al-Fikr.Al-Wasit.1972. Al-Juz al-awwal. Kairo: Majma' al-Lughah al-Arabiyah.Antonio, M. S.2001. Bank Syariah dari Teori ke Praktik . Jakarta: Gema Insani Press dengan Tazkia Cendekia.Ascarya.2012. Akad dan Produk Bank Syariah. Depok: Rajagrafindo Persada.Aziz, M. A.2004. Prospek BMT Berbadan Hukum Koperasi. Jakarta: PINBUK.Buchori, A.2009. Manajemen Bisnis Syariah.Bandung: Alfabeta.Huda, N.2010. Lembaga Keuangan Islam: Tinjauan Teoritis dan Praktik .Jakarta: Prenada Kencana Media Group.Karim, A. A.2004. Bank Islam, Analisis Fiqh dan Keuangan. Jakarta: PT Raja Grafindo.Mubarok, J.2013. Akad Mudharabah.Bandung: Fokus Media.Abidin, I.1987. Radd al-Mukhtar 'ala al-Durr al-Mukhtar. Beirut: Dar Ihya al-Turas.Al-Bahuti. kasyasyaf Al-Qina. Beirut: Dar Al-Fikr.Al-Nawawi. Riyadh al-Shalihin. Beirut: Dar al-Fikr.Al-Wasit.1972. Al-Juz al-awwal. Kairo: Majma' al-Lughah al-Arabiyah.Antonio, M. S.2001. Bank Syariah dari Teori ke Praktik . Jakarta: Gema Insani Press dengan Tazkia Cendekia.Ascarya.2012. Akad dan Produk Bank Syariah. Depok: Rajagrafindo Persada.Aziz, M. A.2004. Prospek BMT Berbadan Hukum Koperasi. Jakarta: PINBUK.Buchori, A.2009. Manajemen Bisnis Syariah. Bandung: Alfabeta.Huda, N.2010. Lembaga Keuangan Islam: Tinjauan Teoritis dan Praktik . Jakarta: Prenada Kencana Media Group.Karim, A. A.2004. Bank Islam, Analisis Fiqh dan Keuangan. Jakarta: PT Raja Grafindo.Mubarok, J.2013. Akad Mudharabah. Bandung: Fokus Media.Muhammad, 2009. Model-model Akad Pembiayaan di Bank Sharia, UII Pres, YogyakartaMUI. 2013. Fatwa DSN-MUINo:01/DSN-MUI/IV/2000 tentang Giro, (online),(http://www.dsnmui.or.id/index.php?mact=News,cntnt 01,detail,0&cntnt01articleid=5&cntnt01returnid=59. diaksestanggal 2 September 2017)MUI. 2013. Fatwa DSN-MUINo:03/DSN-MUI/IV/2000 tentang Deposito Mudharabah, ,(online), (http://www.dsnmui.or.id/index.php?mact=News,cntnt 01,detail,0&cntnt01articleid=5&cntnt01returnid=59. diaksestanggal 2 September 2017)MUI. 2013. Fatwa DSN-MUINo:07/DSN-MUI/IV/2000 tentang Pembiayaan Mudharabah, (online), http://www.dsnmui.or.id/index.php? mact=News,cntnt 01,detail,0&cntnt01articleid =5&cntnt01returnid= 59. diakses tanggal 2 September 2017)Naf'an.2014. Pembiayaan Musyarakah dan Mudharabah. Yogyakarta: Graha Ilmu.Nurul Huda, M. H.2010. Lembaga Keuangan Islam Tinjauan Toritis dan Praktis. Jakarta: Prenada Media Grup.Raharjo, M. D.1999. Islam dan Tantangan Transforasi Sosial Ekonomi . Jakarta: Lembaga Agama dan Studi Filsafah.Ridwan, A. H.2004. BMT dan Bank Islam Instrumen Lembaga Keuangan Syariah. Bandung: Pustaka Bani Quraisy.Riyandono, M. N.2008. Bursa Efek dan Investasi Syariah. Surabaya: Amanah Pustaka.Soemitra, A.2009. Bank dan Lembaga Keuangan Syariah. Jakarta: Prenada Media.Sudarsono, H.2012. Bank dan Lembaga Keuangan Syariah. Yogyakarta: Ekonisia.Wirdyaningsih.2005. Bank dan Asuransi Islam di Indonesia. Jakarta: Kencana.Yin, R. K.2013. Studi kasus: Desain dan Metode. Jakarta: PT. Raja Grafindo.